Patients with chronic hepatitis C and normal transaminases - Pereira, Haydée Marina do Valle; Cavalheiro, Norma de Paula; Tengan, Fátima Mitiko; Melo, Carlos Eduardo; Mello, Evandro Sobroza; Barone, Antônio Alci (Revista do Instituto de Medicina Tropical de São Paulo, 2005)
Hepatitis C virus infection evolves progressively persisting in the majority of patients (85%). Most patients have high ALT (alanine aminotransferase) levels and approximately 25% normal ALT. The latter are usually female and there is no association between genotype and severity of hepatic lesion. Histologic analysis usually shows small lesion and absence or low amount of fibrosis, despite cirrhosis having been reported. Aiming at assessing prevalence, demographic, genotypical and anatomopathological characteristics in patients with normal ALT levels, we have carried out a study of 68 chronic hepatitis C patients between January 1997 and April 2000. There was a prevalence of 13.8% chronic hepatitis C patients with normal ALT levels, 45.6% of which were male and 54.4% female, the mean age being 38 +/- 13 years. We found a predominance of genotype 1 in 84.7% of the patients, genotype 2 in 6.8% and genotype 3 in 10.7%. In 52.9% of the cases liver biopsies revealed liver reaction, periportal activity score 0-1 was observed in 85.3% of the patients and score 2-4 was seen in 14.7%. Structural activity score 0-1 was seen in 73.5% of the patients and score 2-4 in 26.5% of them. Periportal activity >; 2 and structural activity >; 1 was seen in 29%, but steatosis was not seen in 73.5%. Our results suggest the need to revisit for liver biopsy practice in patients with Chronic Hepatitis C and normal transaminases.